2017
DOI: 10.1016/j.nlm.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The basolateral amygdala can mediate the effects of fear memory on sleep independently of fear behavior and the peripheral stress response

Abstract: Fear conditioning associated with inescapable shock training (ST) and fearful context re-exposure (CR) alone can produce significant behavioral fear, a stress response and alterations in subsequent REM sleep. These alterations may vary among animals and are mediated by the basolateral nucleus of the amygdala (BLA). Here, we used the GABAA agonist, muscimol (Mus), to inactivate BLA prior to CR and examined the effects on sleep, freezing and stress-induced hyperthermia (SIH). Wistar rats (n=28) were implanted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 63 publications
5
24
1
Order By: Relevance
“…Using a relatively intense fear conditioning paradigm, we have found that virtually identical footshock stressors and virtually identical fear-conditioned behavioral (freezing) and stress (SIH) responses can be followed by either increases or decreases in REM (e.g., (Wellman et al, 2017; Wellman et al, 2016)). Thus, while studies have reported that sleep has a role in the consolidation of contextual fear memory associated with brief or mild fearful experiences (Reviewed in (Havekes et al, 2015)), our work demonstrates that REM is not necessary for the formation of contextual fear memory associated with intensely stressful experiences, such as those modeled by our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using a relatively intense fear conditioning paradigm, we have found that virtually identical footshock stressors and virtually identical fear-conditioned behavioral (freezing) and stress (SIH) responses can be followed by either increases or decreases in REM (e.g., (Wellman et al, 2017; Wellman et al, 2016)). Thus, while studies have reported that sleep has a role in the consolidation of contextual fear memory associated with brief or mild fearful experiences (Reviewed in (Havekes et al, 2015)), our work demonstrates that REM is not necessary for the formation of contextual fear memory associated with intensely stressful experiences, such as those modeled by our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Post-training inactivation of BLA did block the subsequent fear-conditioned reduction in REM in Vul rats whereas REM in the Res rats was not altered. Pre-context inactivation of BLA also attenuated the reduction in REM in the Vul rats, but did not significantly alter REM in the Res rats (Wellman et al, 2017). The changes in REM were independent of freezing and SIH in both Vul and Res animals regardless of whether BLA was inactivated after shock training or prior to context re-exposure.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations